2020
DOI: 10.1016/j.impact.2020.100211
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress actuated by cellulose nanocrystals and nanofibrils in aquatic organisms of different trophic levels

Abstract: Nanocellulose is a functional material derived from natural carbon-based polymers. These nanomaterials are biodegradable and renewable in nature and hence are seen as environmentally-friendly materials in many applications. The use of such innovative materials is accelerating and inescapable there is a need to test these presumed environmentally-friendly materials with regard to their ecotoxicity. Here, the acute toxicity and the oxidative stress of nanocelluloses as induced to three aquatic organisms of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Oxidative stress caused by the induction of reactive oxygen species has been recognized as the most common pathway affected by nanomaterial exposure and has recently been evoked in NC. 29,40 However, to the best of our knowledge, very little has been achieved due to the limited number of studies on NC fibers in either human models or aquatic species. A significant increase in intracellular ROS levels has been reported by Wang et al 40 in freshwater algae Scenedesmus obliquus, Daphnia magna and Danio rerio upon short-term exposure to wood-based and cotton-based cellulose nanocrystals (4-10 nm and length 100-500 nm), cotton-based CNFs (4-10 nm and length 1000-3000 nm) and cotton-based CNC in the range of 1-10 mg L −1 .…”
Section: Ecotoxicological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress caused by the induction of reactive oxygen species has been recognized as the most common pathway affected by nanomaterial exposure and has recently been evoked in NC. 29,40 However, to the best of our knowledge, very little has been achieved due to the limited number of studies on NC fibers in either human models or aquatic species. A significant increase in intracellular ROS levels has been reported by Wang et al 40 in freshwater algae Scenedesmus obliquus, Daphnia magna and Danio rerio upon short-term exposure to wood-based and cotton-based cellulose nanocrystals (4-10 nm and length 100-500 nm), cotton-based CNFs (4-10 nm and length 1000-3000 nm) and cotton-based CNC in the range of 1-10 mg L −1 .…”
Section: Ecotoxicological Effectsmentioning
confidence: 99%
“…(up to 14 g L −1 CNC and 6 g L −1 for CNF, respectively) even in prolonged exposure (21-day up to 2.06 g L −1 ); however, at low regime and lower concentration (20.6 mg L −1 ), growth and reproduction of daphnids were impaired. 35,39 Increased ROS levels but no mortality were reported in green algae Scenedesmus obliquus, D. magna and zebrafish embryos upon exposure to woodbased CNC, cotton-based CNC and CNF at environmentally relevant concentrations (0.01-10 mg L −1 ) by Wang et al 40 No acute toxicity to CNF extracted from kenaf (Hibiscus cannabinus) was observed in D. magna and adult zebrafish (100 mg L −1 ), but altered swimming behavior was documented in daphnids probably due to CNF gut retention. Conversely, high clearance of CNF (99%) was shown after 60 min of active feeding with CNF in daphnids upon acute exposure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cellulose nanocrystals from different sources did not show developmental or mortality effects on zebrafish, but some oxidative stress at a 0.01 mg L −1 dose was observed. 123 Comparatively, the metal and metal oxide nanoparticles cause significant toxicity due to their physicochemical properties.…”
Section: Potential Impacts Of Polymer-based Nanocomposite Adsorbents ...mentioning
confidence: 99%
“…[31] Within PATROLS, a transgenic fish line for early signaling of NM exposure was developed, facilitating the study of early markers of effect with a fluorescence reporter system. [32,33] This novel testing approach enabled the analysis of oxidative stress, a key mechanism by which NM induces cellular damage, leading to chronic effects of NMs on sensory systems, including olfaction, responses in neuromasts, and ion regulatory systems, and later leading to gill damage. Furthermore, Brinkmann et al (2020) developed a protocol for a germ-free zebrafish larvae test, with clear steps to sterilize embryos of zebrafish, and to allow inoculation of microbes that the larvae encounter, a so-called gnotobiotic technique.…”
Section: Advanced Algae Daphnia and Zebrafish Larvae Testing For Long...mentioning
confidence: 99%